Insect-fungus interactions - Wilding, N. (Neil) (Academic Press, 1989)
The first and only book to summarize this fascinating topic. This symposium volume reviews the current state of knowledge in four principal areas: mycophagy, mutualism, insect spread of plant fungal disease, and insect mycopathology.